FEMINISM MOVEMENT AND THE CHALLENGES OF PATRIARCHY IN INDONESIAN MASS MEDIA - Sukmana, Oman; Nugroho, Agung; Sulastri, Sulastri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the dynamics of the feminist movement in confronting patriarchal challenges within Indonesia’s mass media. Using a descriptive qualitative approach, data were collected through in-depth interviews and observations involving five key informants active in both media and feminist advocacy. The findings indicate that feminist representation in mainstream media remains limited and often biased. Feminist narratives are frequently simplified or distorted, reinforcing stereotypes that align with patriarchal norms. Feminist activists continue to encounter significant barriers, including restricted access to mainstream platforms, editorial limitations, and digital harassment. Despite these obstacles, social media has become an important alternative space for advancing gender equality discourse and amplifying women’s voices. The study emphasizes the urgent need for critical communication strategies, the empowerment of alternative media, and the enhancement of digital literacy to challenge patriarchal dominance. Ultimately, this research underscores the ethical responsibility of the media to construct fair, inclusive, and consistent narratives that support feminist movements and promote gender justice in Indonesia.